Exploring the multidimensional construction of cultural identity through music elements of Chinese Suzhou Pingtan - Li, Yu Kun; Loo, Fung Chiat; Osman, Syuhaily; Yao, Pin Yi (Human Resources Management Academic Research Society (HRMARS), 2024)
Suzhou Pingtan, a traditional performing art from Suzhou, China, skillfully integrates narration, singing and music to convey rich stories and profound emotions. This study is dedicated to profoundly analysing the close relationship between the musical elements of Suzhou Pingtan and the formation of cultural identity. Through a detailed analysis of core aspects such as melody, lyrics, performance style, and cultural context, we explore how Suzhou Pingtan symbolically shapes and reflects the Suzhou region's unique cultural identity and values. Specifically, this research will examine how musical elements such as scales, instrumental, vocal styles and narrative content jointly promote the construction and inheritance of cultural identity in Suzhou Pingtan. Through an in-depth study of this musical tradition, we aim to enhance understanding of the dynamic interplay between music, culture and identity, thereby revealing how Suzhou Pingtan is a carrier of culture in history, representing and passing down the local cultural values, traditions and collective memories.